Acute and Subchronic Toxicity Studies on the Aqueous Extract of the Plant Mixture (Bidens pilosa and Cymbopogon citratus Aerial Parts) in Rat Model - Yannick Carlos Tcheutchoua; Danielle Claude Bilanda; Yolande Sandrine Mengue Ngadena; Paul Désiré Djomeni Dzeufiet; Pascal Emmanuel Owona; Ronald Bidingha á Goufani; Rodrigue Ngapout Fifen; Lohik Mbolang Nguegan; Michel Noubom; Théophile Dimo; Pierre Kamtchouing (Journal of Toxicology)
Bidens pilosa (B. pilosa) and Cymbopogon citratus (C. citratus) are plants used individually or in combination in the traditional treatment of several ailments such as cardiovascular disorders. In order to valorise their traditional use, a toxicological study was conducted on the aqueous extract of the mixture of aerial parts of B. pilosa and C. citratus. The acute and subchronic toxicity studies were conducted according to the OECD 425 and 407 guidelines. Regarding the acute study, the aqueous extract of the mixture of B. pilosa and C. citratus 50 : 50 (2000 and 5000 mg/kg) was administered once to rats of both sexes. In the subchronic study, the aqueous extract of the mixture of B. pilosa and C. citratus (200, 400 and 800 mg/kg) was administered once daily to rats for 28 days. The aqueous extract of the mixture of B. pilosa and C. citratus (2000 and 5000 mg/kg) did not cause death and did not induce any apparent sign of toxicity during the 14 days of observation. The DL50 of the extract is therefore greater than 5000 mg/kg. Taken daily for 28 days, the extract had no significant effect on selected parameters (creatinine, AST, ALT, urea, and uric acid) of renal and hepatic function, as well as on the number of some blood cells. However, the aqueous extract of the mixture of B. pilosa and C. citratus (200 and 400 mg/kg) caused a significant (p < 0.05; p < 0.001, respectively) decrease in creatinine levels in male rats as compared to normal control animals. In females, the aqueous extract of the mixture of B. pilosa and C. citratus (200 and 400 mg/kg) resulted in a significant (p < 0.05) increase in total cholesterol levels as compared to normal control animals. The study showed that the aqueous extract of the mixture of B. pilosa and C. citratus has a low toxicity and does not cause any injury to the liver, kidney, lungs, or spleen.